Greeting and to enquire after’s well-being” in Turkic (Uzbek, Karakalpak, Turkmen) languages - Qutlimuratov Sarmanbek (Genius Journals, 2022)
Although greetings or to enquire after’s well-being are pronounced differently in the speech of each nation, the content of the lexeme, that is, the semantics, has the same meaning in many places. It is inextricably linked to religious beliefs and convictions. Practicing a language while engaging in activities is a great complement to the conversation
Keywords: Language; Communication; inextricably; pronounced